La enseñanza de la Información para la Empresa en la Universidad española. Reflexiones para una orientación académica y profesional de la disciplina - Muñoz Cañavate, Antonio (Documentación de las Ciencias de la Información, 2007)
The last few decades have seen considerable growth in interest in information management. The information and knowledge society has allowed the discipline to leave the restricted world of libraries and archives, independently of whether they belong to the public or private sectors or of whether they are using the latest technologies. The present work deals with the enlargement of information management’s professional orientations and objectives. In particular, it considers the need to assume that companies require special study and analysis as organizations. To create knowledge, they must organize their own repositories of information independently of the support, but they also need to know what there is on the outside so that the decisions they make more efficiently and effectively fulfil their objectives and strategies. Experience shows that the traditional work of documentation scientists does not always match the real needs of a company. We therefore reflect on the changes in society that have given rise to the appearance of jobs that did not exist some years ago, and hence on the need for the world of Library and Documentation Sciences to broaden its academic horizons. The information professional’s role in a company is analyzed, and a study is made to determine which subjects on information management for companies are taught in Library and Documentation Science diplomate and Documentation Science degree courses. Finally, a program is defined for teaching information sources for business.
Keywords: Information Management; Business Information; Business; Training and Education; University; Spain